Consumer engagement with a brand on Facebook - André, Ana Raquel Queirós (2015)
Social media and in particular social Networking Sites have grown in importance and have each day more users. This fact has increased the number of brands on these social networking sites (SNS) trying to engage with their consumers. The purpose of this research is to determine the main motivations for consumers to engage with a brand through Facebook and to study if brand love influences consumer engagement and how these factors (brand love, and consumer engagement) impact brand equity. For this we performed an online survey with 233 valid responses. Correlations analyses were performed in other to study these relations. The results indicate that the principal motivations to engage with a brand through the consumption of content are entertainment, social influence, search for information and trust. The main motivations to interact and participate in a SNS brand page are social influence and personal identity Brand love also influences consumer engagement and these two factors influence brand equity. Theoretical and managerial findings are discussed and directions for further research are given.